Impediment of selenite-induced cataract in rats by combinatorial drug laden liposomal preparation. Issue 1 (1st January 2019) - Zulipiya,; Aximu, Adiya; Aierken, Aikelaimu; Muhemaiti, Paerheti
ABSTRACT: Cataract is the leading cause of blindness globally with surgery being the only form of treatment. But cataract surgery is accompanied by complications, chiefly intra-ocular infections. Hence, preventive nanoformulations may be extremely beneficial. In the present study, novel chitosan-coated liposomal formulations encapsulating a combination of drugs, lanosterol and hesperetin were prepared and characterized. The combinatorial liposomes were prepared by thin film evaporation active extrusion method. The characterization of liposomes was done by transmission electron microscopy, zeta potential, encapsulation efficiency, stability, cytotoxicity and in vitro release studies. The main difference between the chitosan-coated and uncoated combinatorial liposomes is the release of drugs as indicated by the in vitro release studies. The slow and sustained release of the drugs from chitosan-coated ones as against the burst release from uncoated indicates an increased retention time for combinatorial drugs in cornea. This leads to a delay in progression of cataract as seen from in vivo studies. Cytotoxicity studies indicate no cell toxicity of the coating of chitosan or the combination of drugs. Stability studies indicate that there were almost no changes in size, zeta potential and polydispersity index values of the combinatorial liposomes upon storage at room temperature for 60 days. Another important study is the estimation of antioxidant defense system. The estimated values of glutathione reductase, malondialdehyde and chief antioxidant enzymes point toward an upregulation of antioxidant defense system. From the results, it may be concluded that novel chitosan-coated combinatorial liposomes are effective in delaying or preventing of cataract.